Comparison of the Filtration Efficiency of Different Face Masks Against Aerosols - Stahl, Connor; Frederick, Kevin; Chaudhary, Sachin; Morton, Christopher J.; Loy, Douglas; Muralidharan, Krishna; Sorooshian, Armin; Parthasarathy, Sairam (Frontiers in Medicine, 2021)
Background: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic can spread through virus-containing aerosols (≤ 5 μm) and larger airborne droplets. Quantifying filtration efficiency of different kinds of masks and linings for aerosols that fall within the most penetrating particle size (80 – 400 nm) is critical to limiting viral transmission. The objective of our experiment was to compare the “real-world” filtering efficiency of different face masks for fine aerosols (350 nm) in laboratory simulations. Methods: We performed a simulated bench test that measured the filtering efficiency of N95 versus N99 masks with elastomeric lining in relation to baseline (“background”) aerosol generation. A mannequin head was placed within a chamber and was attached to an artificial lung simulator. Particles of known size (350 ± 6 nm aerodynamic diameter) were aerosolized into the chamber while simulating breathing at physiological settings of tidal volume, respiratory rate, and airflow. Particle counts were measured between the mannequin head and the lung simulator at the tracheal airway location. Results: Baseline particle counts without a filter (background) were 2935 ± 555 (SD) cm-3, while the N95 (1348 ± 92 cm-3) and N99 mask with elastomeric lining (279 ± 164 cm-3; p < 0.0001) exhibit lower counts due to filtration. Conclusion: The filtration efficiency of the N95 (54.1%) and N99 (90.5%) masks were lower than the filtration efficiency rating. N99 masks with elastomeric lining exhibit greater filtration efficiency than N95 masks without elastomeric lining and may be preferred to contain the spread of SARS-CoV-2 infection.